Heterosis and Variation in Reproductive Parameters of Reciprocal F1 Hybrids between Eucalyptus tereticornis Sm. And E. Camaldulensis Dehn - Venkatesh, C. S.; Thapliyal, R. C. (Indian Forester, 1993)
F1 hybrids belonging to two reciprocal interspecific crosses between Eucalyptus tereticornis and E. camaldulensis which had proved conspicuously heterotic in growth rate and flowering precocity also proved heterotically superior in flowering density, seed production and seed weight. While in flowering precocity FRI-5 (E. camaldulensis x E. tereticornis) was heterotic over the mid-parent only, in height, diameter, flowering density, seed production and seed weight, both the hybrid classes were superior over the better E. tereticornis parental progenies. Hybrid seed was highiyviable and its germination energy was higher than the mid-parental value. Since all the investigated quantitative traits varied considerably in the F1 generation itself and since no correlations were observed among them it must be inferred that independent polygenic systems control their inheritance. Strong maternal effects were also evident for various characters in the hybrids. While high and sustained heterotic growth superiority could be directly utilized for speedier and higher wood or phytomass production in mini-rotation pulp and energy forest plantations on suitable sites, heterosis in flowering precocity and various seed characters can facilitate accelerated breeding of advanced-generations and recurrent selection.